If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7+7x=6(-2x+3)-3(3x-8)
We move all terms to the left:
-7+7x-(6(-2x+3)-3(3x-8))=0
We calculate terms in parentheses: -(6(-2x+3)-3(3x-8)), so:We get rid of parentheses
6(-2x+3)-3(3x-8)
We multiply parentheses
-12x-9x+18+24
We add all the numbers together, and all the variables
-21x+42
Back to the equation:
-(-21x+42)
7x+21x-42-7=0
We add all the numbers together, and all the variables
28x-49=0
We move all terms containing x to the left, all other terms to the right
28x=49
x=49/28
x=1+3/4
| X=43x+1=13-x | | 3x+1=13-4 | | 6m+35=-43 | | W(t)=80+5,4t | | 3n+20=2n+20 | | 2x/5-1/5+3/4.x-2/3-6=0 | | 13+23=-4(7x-9) | | 10x=3x-6 | | 7x+11x-5x=65 | | 2x+10+x+8=180 | | 3x+8x+5x=6x+80 | | x^-24=5x | | 2x=18-1 | | 2x^+75×-15=0 | | 6x+9x=6x+50 | | 25x^=36 | | 3x-2x+5=-10 | | 3x^2+6x+x^2-2x+1=x+1 | | X-2=-195+5x-3 | | x=-2,x=2 | | C=5÷9(f-32) | | 2x-4x+16=-30 | | 2x/5+1/4=-1/2+1x/10 | | 13=3/6k | | -3=-2x=19 | | x²-51=0 | | 7=7z+6z | | x²-3x-7x-21+10x-30=0 | | 1/3x=6/13 | | -4(2x+3)=-2x+6-(8x+2) | | 3^(5*x)=375 | | 10-2(2x-2)=-4 |